CRITICAL ANALYSIS ON INTERNATIONAL LAW’S FRAMEWORK TO PIRACY - Sabatira, Febryani; Knudsen, Gustav Damgaard; Jaya, Belardo Prasetya Mega; Lutfi, Muhamad Uut; Jaelani, Achmad (Tirtayasa Journal of International Law, 2025)
Piracy remains a formidable challenge to maritime security and global trade, thriving on jurisdictional ambiguities and exposing vulnerabilities in international governance. Despite its recognition under the United Nations Convention on the Law of the Sea (LOSC) as a crime of hostis humani generis subject to universal jurisdiction, significant gaps persist in its enforcement. The LOSC’s limitations, such as its strict criteria for defining piracy, often hinder effective prosecution. Supplementing this framework, the Suppression of Unlawful Acts Against the Safety of Maritime Navigation (SUA) Convention addresses critical shortcomings, including the jurisdictional constraints of the LOSC, by enabling broader prosecutorial scope and facilitating extradition agreements. However, its limited ratification by key maritime states undermines its potential impact. This study undertakes a critical analysis of these legal frameworks, highlighting their respective contributions and deficiencies in combating piracy. The analysis further emphasizes the urgent need for cohesive international collaboration, harmonized enforcement protocols, and the adoption of innovative legal mechanisms to counter the evolving nature of maritime piracy